Pengembangan Media Pembelajaran Magic Qur-Dis Berbasis Thunkable pada Pembelajaran al-Qur’an Hadits di MTsN 1 Kediri - Vivi Hafidhoh Munir; Hidayatur Rohmah (ANWARUL, 2026)
Rapid technological development has encouraged the renewal and use of digital media in the learning process, including in the Al-Qur’an Hadith subject. However, Al-Qur’an Hadith learning at MTsN 1 Kediri still faces limitations in interactive learning media that can optimally support students’ understanding. This study aims to develop Thunkable-based MAGIC QUR-DIS interactive learning media to assist the delivery of material and improve students’ understanding in Al-Qur’an Hadith learning. This study used the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, planning, development, implementation, and evaluation. The subjects of this study were students at MTsN 1 Kediri. Data were collected through interviews, media validation, material validation, and student response questionnaires. The results showed that media validation obtained a percentage of 85% in the very valid category, whereas material validation obtained a percentage of 87.5% in the very valid category. Students’ responses to the MAGIC QUR-DIS media reached 91.13% in the very practical category. The conclusion of this study affirms that Thunkable-based MAGIC QUR-DIS media is feasible and practical for supporting Al-Qur’an Hadith learning. The implications of this study indicate that the development of technology-based learning media can serve as an innovative solution for teachers in creating learning that is more engaging, interactive, and able to increase students’ learning interest. Keywords: Media Development; Interactive Learning Media; MAGIC QUR-DIS; Thunkable; Al-Qur’an Hadith